DUKAKIS ENDORSES PENSION REFORM BILL - VENNOCHI,J (Tufts Archival Research Center, 2007)
Illegible/Difficult to Read; Article in the Boston Globe detailing the changes made by Gov. Dukakis to the Massachusetts Pension System. Targets specifically disability benefits. Includes discussion of the original draft, which contained a provision that fire fighters who smoke must prove that any heart or lung problems are job related, not smoking related.